CHAOS, SOCIAL RECONFIGURATION AND CONFLICTS: A POST- MODERNIST READING OF COETZEE’S NOVEL DISGRACE - Najeem Khan; Rubina Hussain; Saeed Ur Rahman; Reham Sana (Policy Research Journal, 2025)
This research explores the aftermath of apartheid and its impact on characters in Coetzee's Disgrace, focusing on post-apartheid social unrest and the shift from white imperial grand narratives to local mini-narratives. It highlights the rising female consciousness, the scrutiny of white hegemony and patriarchy, and the fragile social cohesion between black and white characters. The study analyzes the novel's causes of chaos, fragmentation, and conflict, mainly through the downfall of the anti-hero David Lurie, symbolizing the collapse of white supremacy and Eurocentric values. The research uses a postmodern framework to examine how these conflicts reflect psychological anguish and shifting subjectivity. The findings underscore the complexities of multiculturalism and peaceful coexistence in post-apartheid South Africa, offering new insights into the cultural and political tensions that continue to shape the nation's identity.